A clinical study on head meridian massage to relieve tension type headache in patients with anxiety disorders (头部经穴推拿缓解焦虑障碍患者紧张性头痛的临床研究) - WEI Hongmei (韦红梅); CHEN Yanfen (陈燕芬); LUO Tianyun (罗添云); YE Junrong (叶君荣); XIONG Linghui (熊令辉); LONG Xuxing (龙绪星); ZHOU Peilin (周沛林); ZHANG Xin (张辛) (中西医结合护理)
Objective To evaluate the effect of head meridian massage therapy on relieving tension type headache (TTH) symptoms in patients with anxiety disorders. Methods Totally 81 patients with anxiety disorder and TTH were randomly divided into an experimental group of 40 cases and a control group of 41 cases. The control group was given conventional treatment and nursing care, and the experimental group was treated with head meridian massage on the basis of the control group. The visual analogue scale (VAS), Hamilton Anxiety Scale (HAMA) and self-made efficacy standards were used to compare the headache degree, anxiety and clinical efficacy of the two groups before and after treatment. At the same time, the number of headache attacks within one week after the end of the treatment was compared between the two groups. Results After the intervention, the VAS score and HAMA score of the experimental group were lower than those of the control group, and the total effective rate of the experimental group was higher than that of the control group(P＜0. 05). The number of headache attacks in the experimental group was less than that of the control group within one week after the treatment course(P＜0. 05). Conclusion Head meridian massage can effectively relieve tension headache symptoms in patients with anxiety disorders. (目的 评价头部经穴推拿疗法缓解焦虑障碍患者紧张性头痛(TTH)症状的效果。方法 81例焦虑障碍伴头痛的患者随机分为研究组40例和对照组41例。对照组给予常规治疗和护理, 研究组在对照组基础上应用头部经穴推拿疗法。通过视觉模拟评分法(VAS)、汉密尔顿焦虑量表(HAMA)以及自制疗效标准比较2组治疗前和治疗后的头痛程度、焦虑情况和干预效果, 比较2组疗程结束后1周内头痛发作次数。结果 干预后, 研究组头痛VAS评分和HAMA评分低于对照组, 差异有统计学意义(P＜0. 05)。研究组总有效率高于对照组, 差异有统计学意义(P＜0. 05)。疗程结束后1周内研究组头痛发作次数少于对照组, 差异有统计学意义(P<0. 05)。结论 头部经穴推拿疗法能有效缓解焦虑障碍患者紧张性头痛症状。)